Primary omental torsion: A case report - Scabini, Stefano (Baishideng Publishing Group Co., Limited, 2011)
A patient presented with an acute abdomen at the Emergency Department. The patient, a 69-year-old man, was admitted and underwent surgery with a provisional diagnosis of acute appendicitis. During surgery, omental torsion was diagnosed and the involved omentum was removed. The patient had no previous surgical history. Omental torsion is a rare cause of acute abdomen in children and adults who may present with various signs and symptoms; a preoperative diagnosis may therefore be difficult and can usually only be established during surgery.